Maintaining Humanism in Virtual Clinical Education: Implementation of Meaningful Virtual Simulations - Nair, Nisha (European Journal of Applied Sciences, 2021)
Virtual human simulation is a recent addition to the educational arsenal that involves human role players interacting with learners in a wide range of experiential learning via virtual platforms. Standardized or simulated virtual patients (SVPs) portray actual patients presenting specific clinical scenarios. After the simulation, SVPs can provide timely feedback to students to help improve clinical performance. A pilot study was done with 3rd-semester undergraduate nursing students during their maternal newborn practicum. The scenario was developed based on clinical experience using cognitive task analysis. Participants provided feedback (face and content validity) after participating in the simulated tasks. The performance of virtual patients in the scenario was evaluated for consistency reliability by examiners. Inter-rater reliability was also tested to determine the agreement between examiners' evaluations. The study will extend an ongoing effort to involve multiple cohorts by implementing the Virtual Patient Simulation Tool to make evidence-based, shared decisions and involve patient input in the design of the VP simulation.